Twist-Induced Epithelial-to-Mesenchymal Transition Confers Specific Metabolic and Mitochondrial Alterations - Haleigh N. Parker; Kayla L. Haberman; Tolulope Ojo; Juli Watkins; Adhwaitha Nambiar; Kayla Morales; Bernd Zechmann; Joseph H. Taube (Cells)
Cells undergo significant epigenetic and phenotypic change during the epithelial-to-mesenchymal transition (EMT), a process observed in development, wound healing, and cancer metastasis. EMT confers several advantageous characteristics, including enhanced migration and invasion, resistance to cell death, and altered metabolism. In disease, these adaptations could be leveraged as therapeutic targets. Here, we analyze Twist-induced EMT in non-transformed HMLE cells as well as a breast cancer cell line with (MDA-MB-231) and without (MCF7) EMT features to compare differences in metabolic pathways and mitochondrial morphology. Analysis of oxidative and glycolytic metabolism reveals a general EMT-associated glycolytic metabolic phenotype accompanied by increased ATP production. Furthermore, a decrease in mitochondrial size was also associated with EMT-positive cells. However, mitochondrial elongation and spatial dynamics were not consistently altered, as HMLE Twist cells exhibit more rounded and dispersed mitochondria compared to control, while MDA-MB-231 cells exhibit more elongated and clustered mitochondria compared to MCF7 cells. These results provide further insight as to the contextual nature of EMT conferred properties.